Developing methods to identify resilience and improve communication about diagnosis in pediatric primary care - Rasooly, Irit R.; Marshall, Trisha L.; Cifra, Christina L.; Catchpole, Ken; Kuzma, Nicholas C.; Brady, Patrick W.; Melton, Katherine; Khan, Alisa; Chien, Alyna T.; Lipstein, Ellen A.; Landrigan, Christopher P.; Walsh, Kathleen E. (Frontiers in Medicine, 2024)
Communication underlies every stage of the diagnostic process. The Dialogue Study aims to characterize the pediatric diagnostic journey, focusing on communication as a source of resilience, in order to ultimately develop and test the efficacy of a structured patient-centered communication intervention in improving outpatient diagnostic safety. In this manuscript, we will describe protocols, data collection instruments, methods, analytic approaches, and theoretical frameworks to be used in to characterize the patient journey in the Dialogue Study. Our approach to characterization of the patient journey will attend to patient and structural factors, like race and racism, and language and language access, before developing interventions. Our mixed-methods approach is informed by the Systems Engineering Initiative for Patient Safety (SEIPS) 3.0 framework (which describes the sociotechnical system underpinning diagnoses within the broader context of multiple interactions with different care settings over time) and the Safety II framework (which seeks to understand successful and unsuccessful adaptations to ongoing changes in demand and capacity within the healthcare system). We will assess the validity of different methods to detect diagnostic errors along the diagnostic journey. In doing so, we will emphasize the importance of viewing the diagnostic process as the product of communications situated in systems-of-work that are constantly adapting to everyday challenges.